1847 Ga. Laws 138, An Act To Incorporate The Evergreen Cemetery Company Of Bonaventure, § 5 - (:unkn) unknown (General Publisher, 1847)
Prohibited shooting or discharging any gun or other firearms within the cemetary limits. Violators guilty of a misdemeanor.
--
Keywords: DISCHARGE